Modelling and control of the roll-stabilised control unit of a rotary steerable system directional drilling tool - Alturbeh, Hamid; Whidborne, James F.; Luk, Patrick Chi-Kwong; Bayliss, Martin T. (Institution of Engineering and Technology (IET), 2019)
A directional drilling tool control unit whose design is based on servo control of a rotary valve using the roll-stabilised instrumented system approach has been successfully used in oil fields for over 20 years. Here, field-oriented control (FOC) is applied to cascaded voltage regulation and servo control using an open-loop plant model of the roll-stabilised control unit. The servo control is applied to the rotary valve so that drilling mud is ported in a geostationary direction despite the rotation of the drill string and the bottom hole assembly of the rotary steerable system. Voltage regulation is applied in order to provide a DC voltage bus for the servo control of the valve. A torquer or alternator, which is a type of permanent magnet synchronous machine, is the core of the roll stabilised control unit. So, a mathematical model of the torquer is derived. An FOC scheme is proposed for servo control and to provide a DC regulated voltage using the torquers. The algorithm is tested in MATLAB/Simulink.
Keywords: servomechanisms; machine control; machine vector control; robust control; permanent magnet machines; drilling; voltage control; control system synthesis; synchronous machines; closed loop systems; drilling (geotechnical);; permanent magnet motors; motion control; valves